Uso de indicadores geoquímicos e biológicos para avaliação da qualidade ambiental da APA Pratigi, Ba - Silva, Anna Carolina de Freitas Santos da (2022)
Environmental contamination by trace metals is considered a problem because they are toxic contaminants that persist for decades in the environment and are associated with bioaccumulation and biomagnification processes. In sediments, the accumulation and distribution of trace metals occur by complex processes. In crabs, chemical analysis of gills, hepatopancreas and muscle provides information on the quality of the external environment. The performance of ecotoxicological bioassays with the liquid fraction of the sediment allows the evaluation of the effects of toxic substances. In the estuary of the Serinhaém river there are mangroves, subject to the impacts of human activities carried out in the region. Thus, through this research, the objective was to evaluate the environmental quality of the Serinhaém River estuary, Pratigi APA, BA, through the quantification of trace metals in sediment and crabs, and application of ecotoxicological tests. For this, sediments and crabs of the Cardisoma guanhumi species were collected at sampling points in the estuary. Bioassays were conducted with exposure of marine microalgae Thalassiosira pseudonana and copepod Nitokra sp. to the elutriate. The chemical analysis corresponded to the steps of chemical digestion and determination of metals by ICP-OES. The decreasing order of metal levels in sediments corresponded to: Al > Fe > P > Mn > Cr > Zn > Pb > Ni > Cu, with Cr and Ni being above the limit established by CONAMA nº 454/2012 for the P1. Comparison of values with studies for the estuary showed higher concentrations of Cr, Cu, Ni and Pb obtained in this work. The microalgae test showed high toxicity for P1 and P2. In the copepod bioassay, there was high toxicity for offspring also for P1 and differences in the number of individuals between life stages. Fe was the most concentrated element in C. guanhumi (Fe > Zn > Cr > Ni > Cu > Mn), and the bioaccumulation factor was not significant, although Cr concentrations are above Brazilian legislation. The general analysis of the data allowed the evaluation of the quality of the Serinhaém River estuary, demonstrating that this environment may be suffering impacts from anthropogenic pressures.